Abordagens de evolução dirigida para aumento da eficiência catalítica da enzima terapêutica L-asparaginase II de Bacillus subtilis - Silva, João Matheus Fonteles (2025)
L-asparaginase II is an enzyme used in routine chemotherapy for the treatment of acute lymphoblastic leukaemia (ALL). Currently, the main commercial formulations of L-asparaginases (L-ASNases) are derived from the bacteria Escherichia coli and Erwinia chrysanthemi, but they are associated with side effects such as immunogenicity, hypersensitivity and other adverse effects. It is therefore necessary to apply techniques aimed at developing L-ASNases with improved activity, stability and affinity. Directed protein evolution is a tool that allows the construction of mutant gene libraries using techniques such as error-prone PCR (epPCR) or in vitro gene recombination. When combined with an efficient screening method, it is possible to select the mutants with the best performance for a given property of interest and obtain an improved protein. The aim of this work is to use directed evolution methods to improve the catalytic efficiency of L-asparaginase II from Bacillus subtilis (BsAII). EpPCR was used to generate three libraries of mutants of the ansZ gene encoding L-ASNase with different mutation rates. Based on the analysis of the mutations, the most appropriate mutation rate of approximately 1% was determined. The mutated ansZ genes were cloned into periplasmic constitutive expression vectors and inserted into E. coli cells. The screening methods were divided into three different stages, starting with a selection in solid medium, followed by an enzymatic assay of the post-expression cell-free broth, and ending with tests of asparaginase activity and determination of the kinetic parameters of the recombinant proteins. The mutants nº 1 (BsAII-S1-Mut93) and nº 2 (BsAII-S2-Mut26) selected by the screening method were expressed in the pET28a vector. The expression yield, activity evaluation and determination of kinetic parameters of the mutants were compared with those of native BsAII. BsAII-S2-Mut26 showed a 2-fold higher expression yield and similar asparaginase activity and affinity to native BsAII. On the other hand, BsAII-S1-Mut93 showed a similar expression yield, 5-fold lower asparaginase activity and 3-fold lower Michaelis-Menten constant (KM) compared to native BsAII. Although directed evolution techniques have great potential for the development of improved enzymes, more efficient mutant selection and screening conditions need to be standardised in order to obtain promising Bacillus subtilis L-asparaginase II clones for therapeutic applications.